Beyond flowering time: diverse roles of an APETALA2‐like transcription factor in shoot architecture and perennial traits. Issue 1 (1st September 2020) - Zhou, Yanhao; Gan, Xiangchao; Viñegra de la Torre, Natanael; Neumann, Ulla; Albani, Maria C.
Summary: Polycarpic perennials maintain vegetative growth after flowering. PERPETUAL FLOWERING 1 ( PEP1 ), the orthologue of FLOWERING LOCUS C ( FLC ) in Arabis alpina regulates flowering and contributes to polycarpy in a vernalisation‐dependent pathway. pep1 mutants do not require vernalisation to flower and have reduced return to vegetative growth as all of their axillary branches become reproductive. To identify additional genes that regulate flowering and contribute to perennial traits we performed an enhancer screen of pep1 . Using mapping‐by‐sequencing, we cloned a mutant ( enhancer of pep1‐055, eop055 ), performed transcriptome analysis and physiologically characterised the role it plays on perennial traits in an introgression line carrying the eop055 mutation and a functional PEP1 wild‐type allele. eop055 flowers earlier than pep1 and carries a lesion in the A. alpina orthologue of the APETALA2 ( AP2 )‐like gene, TARGET OF EAT2 ( AaTOE2 ). AaTOE2 is a floral repressor and acts upstream of SQUAMOSA PROMOTER‐BINDING PROTEIN‐LIKE 5 (AaSPL5). In the wild‐type background, which requires cold treatment to flower, AaTOE2 regulates the age‐dependent response to vernalisation. In addition, AaTOE2 ensures the maintenance of vegetative growth by delaying axillary meristem initiation and repressing flowering of axillary buds before and during cold exposure. We conclude that AaTOE2 is instrumental in fine tuning different developmental traits in the perennial life cycle of A. alpina .